Thioredoxin VdTrx1, an unconventional secreted protein, is a virulence factor in Verticillium dahliae - Tian, Li; Zhuang, Jing; Li, Jun-Jiao; Zhu, He; Klosterman, Steven J.; Dai, Xiao-Feng; Chen, Jie-Yin; Subbarao, Krishna V.; Zhang, Dan-Dan (Frontiers in Microbiology, 2023)
Understanding how plant pathogenic fungi adapt to their hosts is of critical importance to securing optimal crop productivity. In response to pathogenic attack, plants produce reactive oxygen species (ROS) as part of a multipronged defense response. Pathogens in turn have evolved ROS scavenging mechanisms to undermine host defence. Thioredoxins (Trx) are highly conserved oxidoreductase enzymes with a dithiol-disulfide active site, and function as antioxidants to protect cells against free radicals, such as ROS. However, the roles of thioredoxins in Verticillium dahliae, an important vascular pathogen, are not clear. Through proteomics analyses, we identified a putative thioredoxin (VdTrx1) lacking a signal peptide. VdTrx1 was present in the exoproteome of V. dahliae cultured in the presence of host tissues, a finding that suggested that it plays a role in host-pathogen interactions. We constructed a VdTrx1 deletion mutant ΔVdTrx1 that exhibited significantly higher sensitivity to ROS stress, H2O2, and tert-butyl hydroperoxide (t-BOOH). In vivo assays by live-cell imaging and in vitro assays by western blotting revealed that while VdTrx1 lacking the signal peptide can be localized within V. dahliae cells, VdTrx1 can also be secreted unconventionally depending on VdVps36, a member of the ESCRT-II protein complex. The ΔVdTrx1 strain was unable to scavenge host-generated extracellular ROS fully during host invasion. Deletion of VdTrx1 resulted in higher intracellular ROS levels of V. dahliae mycelium, displayed impaired conidial production, and showed significantly reduced virulence on Gossypium hirsutum, Arabidopsis thaliana and Nicotiana benthamiana. Thus, VdTrx1 acts as a virulence factor in V. dahliae.